The practice of Lectio Divina in response the challenges of contemporary social realities - Yung-Boon, Verona Cha, OSB (Animo Repository, 2004)
The present study aims to investigate how the Missionary Benedictine Sisters of the Philippines enflesh their charism in practice of Lectio Divina in responding to the challenges of contemporary social realities. Mainly, this study unveiled how Lectio Divina promotes the missionary vocation of the Benedictine Sisters in their apostolic life and how it deepens the meaning and purpose of their life experiences in relation to the pressing current social realities. Specifically, this study addressed the following questions: 1. What is the meaning of Lectio Divina to the Sisters in their apostolate? 2. Does Lectio Divina contribute to the spiritual well being of the Sisters? 3. Is the process of Lectio Divina relevant to the Sisters’ work of evangelization? 4. Does the Lectio divina help the Missionary Benedictine Sisters respond appropriately to the signs of times? 5. What challenges are encountered by these Sisters in practicing Lectio Divina? This study employed a survey research that was descriptive. The method of sampling used was purposive. Of the total 177 Sisters, 35 Sisters were chosen to be the respondents based on age, apostolate, and profession year. Two instruments were deemed appropriate measures for the study. The first was a survey questionnaire utilizing scale. The second was an interview guide. The salient findings of this were the following: 1. Lectio Divina gives meaning to the Sisters’ vocation, it strengthens their faith and enables them to grow in Christ. They experience through Lectio Divina its significance and relatedness to their missionary life and service. 2. Lectio Divina contributes to their spiritual well being on the personal vi aspect and strengthens their interconnectedness to other Sisters and to the people. 3.Contemplative prayer greatly influences their effectiveness in their work of evangelization. The apostolate leads them to a deeper relationship with God. 4. There is a connection of Lectio Divina with social realties, and the Sisters respond appropriately to the signs of the times. 5. The challenges the Sisters are faced with are a definite time for Lectio Divina, rigidity in practicing Lectio Divina, allowing Lectio Divina to influence their resolution with people, their resolution of conflicts and tensions which made them more mature, and the practice of Lectio Divina as a lived experience of being rooted in the Word of God. Moreover, the Benedictine Sisters’ practice of Lectio Divina promotes their vocation, deepens their relationship with others, it makes them listen, discern and respond to the will of God in responding to the challenges of contemporary social realities. Therefore, Lectio Divina should continue as a vital force among the Benedictine Sisters to inspire, console, challenge and assist them in their vocation.